Avaliação histeroscópica em pacientes com infertilidade - Lasmar, Ricardo Bassil; Barrozo, Paulo Roberto Mussel; Parente, Raphael Câmara Medeiros; Lasmar, Bernardo Portugal; Rosa, Daniela Baltarda; Penna, Ivan Araujo; Dias, Rogerio [UNESP] (FapUNIFESP (SciELO), 2010)
PURPOSE: to describe hysteroscopy findings in infertile patients. METHODS: this was a retrospective series of 953 patients with diagnosis of infertility evaluated by hysteroscopy. A total of 957 patients investigated for infertility were subjected to hysteroscopy, preferentially during the first phase of the menstrual cycle. When necessary, directed biopsies (under direct visualization during the exam) or guided biopsies were obtained using a Novak curette after defining the site to be biopsied during the hysteroscopic examination. Outcome frequencies were determined as percentages, and the χ2 test was used for the correlations. The statistical software EpiInfo 2000 (CDC) was used for data analysis. RESULTS: a normal uterine cavity was detected in 436 cases (45.8%). This was the most frequent diagnosis for women with primary infertility and for women with one or no abortion (p<0.05). Abnormal findings were obtained in 517 of 953 cases (54.2%), including intrauterine synechiae in 185 patients (19.4%), endometrial polyps in 115 (12.1%), endocervical polyps in 66 (6.0%), submucosal myomas in 47 (4.9%), endometrial hyperplasia in 39 (4.1%), adenomyosis in five (0.5%), endometritis (with histopathological confirmation) in four (0.4%), endometrial bone metaplasia in two (0.4%), and cancer of the endometrium in one case (0.1%). Morphological and functional changes of the uterus were detected in 5.6% of the cases, including uterine malformations in 32 (3.4%) and isthmus-cervical incompetence in 21 (2.2%). CONCLUSIONS: intrauterine synechiae were the most frequent abnormal findings in patients evaluated for infertility. Patients with a history of abortion and infertility should be submitted to hysteroscopy in order to rule out intrauterine synechiae as a possible cause of infertility.
Hysteroscopic evaluation in patients with infertility
Keywords: Endometrium; Hysteroscopy/methods; Infertility/diagnosis; Polyps; Tissue adhesions; adolescent; adult; female; female infertility; human; hysteroscopy; middle aged; retrospective study; Adolescent; Adult; Female; Humans; Hysteroscopy; Infertility, Female; Middle Aged; Retrospective Studies; Young Adult